Bi-functional Ni-doped La2O3 nanosheets: their enhanced photocatalytic performance and antibacterial properties. (28th July 2022) - Arshad, Aqsa; Siddique, Sadaf; Shahid, M; Zulqurnain, M; Niazi, R K; Mansoor, Q; Nadeem, K
Abstract: Contaminated water and antibiotic resistance are global threats that need urgent attention. In this work, we present the sunlight-induced removal of methyl violet (MV) and antibacterial properties of neat La2 O3 nanoribbons and Ni (1%, 3%, 5%)-doped La2 O3 nanosheets. The increased concentration of Ni dopant not only induces the morphological transformation to quasi-2D-surface-like nanosheets but also greatly improves the optical properties by reducing the bandgap of La2 O3, which synergistically serves to enhance the photocatalytic activity for the degradation of MV. The 5% Ni-doped La2 O3 nanosheets exhibit the maximum photocatalytic efficiency, i.e. 99.15% compared to La2 O3 (29%) nanoribbons alone, which makes them an exceptional material for the decontamination of MV polluted water. In addition, at the optimized concentration of Ni, La2 O3 nanosheets show robust antibacterial activity against P. aeruginosa and S. aureus by inhibiting 83.14% and 84.88% growth, respectively. 5% Ni-doped La2 O3 can be a potential bi-functional nanocatalyst and a novel antibacterial material owing to its unique sheet-like morphology that provides high surface interaction with the bacteria and a greater number of adsorption sites for the contaminant dye.